2011
DOI: 10.1002/qua.22644
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and vibrational frequencies of the helical polypeptide complexes with ligand molecules

Abstract: The complexes of alpha helical polypeptides and individual molecules of water, acetonitrile, and 1,4-dioxane have been investigated. We used 16-mer of polyalanine (PA), polyglutamic acid (PGA) and poly-c-benzyl-L-glutamate (PBG). Full geometry optimization was performed for polypeptides and their complexes with ligands, each structure has been characterized by the vibrational analysis and the interaction energy including the correction for zero point vibrational energy. Polyalanine creates by single complex wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…As early as 1937, it was found that a linear relationship exists between H‐bond strength and the shift in the IR H–X stretching frequency, termed the Badger–Bauer rule (Figure ) . The qualitative correlation between H‐bond strengths and stretching frequencies has been observed in many chemical systems . Although a single linear relationship does not hold throughout the many diverse types of H‐bonding, satisfactory linear correlations between enthalpy of H‐bond formation, the IR stretching frequency shift, and the X–H bond elongation were found for structurally related compounds …”
Section: Spectroscopic Signatures Of Hyperconjugationmentioning
confidence: 99%
“…As early as 1937, it was found that a linear relationship exists between H‐bond strength and the shift in the IR H–X stretching frequency, termed the Badger–Bauer rule (Figure ) . The qualitative correlation between H‐bond strengths and stretching frequencies has been observed in many chemical systems . Although a single linear relationship does not hold throughout the many diverse types of H‐bonding, satisfactory linear correlations between enthalpy of H‐bond formation, the IR stretching frequency shift, and the X–H bond elongation were found for structurally related compounds …”
Section: Spectroscopic Signatures Of Hyperconjugationmentioning
confidence: 99%
“…In the initially published paper, it was proposed that the enthalpy of formation of hydrogen bonds, Δ H , was linearly related to the infrared frequency shifts, Δν for hydroxylic electron acceptors involved in such hydrogen bonding. Since this time, it has been extensively used to correlate experimentally determined red frequency shifts of B–HO– and related stretching vibrations with intermolecular binding strengths for a large range of hydrogen bonded acceptors, B. A number of models have also been developed theoretically to account for the basis of the Badger–Bauer relationship. Further applications have, in addition, involved a wide range of studies including H–X red frequency shifts with force constants or bond length changes. There have been varying degrees of success with such correlations, in part due to a number of factors such as solvent and steric effects in experimental studies and the influence of anharmonicity. ,,, Despite these issues, Badger–Bauer relationships still continue to be invoked in a wide range of applications. These have also included proton acceptor carbonyl frequency shifts , because of the facility of experimental measurements. In particular, spectroscopically determined frequency shifts on complexation are used as a means of qualitatively or quantitatively probing of the strength of noncovalent interactions as well as the environment of hydrogen bonded interactions.…”
Section: Introductionmentioning
confidence: 99%
“…68 Our group 913 and others 1417 have reported density functional theory (DFT) calculations on the stabilities of these helices without solvation, and solvated using the SM5.2 aqueous solvation model. 18 Kubelka has reported the effects of explicit waters on vibrational spectra of helices, 19 Ermakova has reported other studies of α-helices 20,21 and Ireta has reported studies of β-sheets 22 interacting with individual water molecules…”
mentioning
confidence: 99%